Summer on Blossom Street - Macomber, Debbie (Don Mills, Ont. : MIRA Books, 2009)
Upbeat cancer survivor Lydia and her pragmatic sister, Margaret, start a "Knit to Quit" group in their Blossom Street yarn store in Seattle, bringing in a delightful assortment of customers for weekly self-help sessions, including a local baker who wants a baby as much as Lydia does, a super-stressed chocolate magnate who takes the knitting class after his doctor suggests it, and a young woman who is trying to quit obsessing about a broken engagement.
Keywords: Knitting; Knitters (Persons); Cancer -- Patients; Female friendship; Seattle (Wash.); Domestic fiction; Love stories